2023
DOI: 10.3390/jtaer18030071
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of AI Adoption, IoT Edge, and Adaptive Resilience to Explain Digital Innovation: Evidence from German Family-Owned SMEs

Irfan Saleem,
Shah Md. Safiul Hoque,
Rubeena Tashfeen
et al.

Abstract: This study aims to discover how artificial intelligence adoption in notion (AI) plays a role in digital innovation using the theoretical foundation of diffusion of innovations and effectuation theories. The current research also investigates the moderating role of other edge Internet of Things (IoT) and the mediating role of adaptive resilience. The data collection is performed using a survey conducted among employees of family-owned SMEs. The findings reveal that AI forecasts digital innovation through adapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The external factors are associated with new market opportunities [47,50], institutional change [44], technological innovation [31,35,43], and other perspectives of the industry [34]. These studies are associated with the energy sector [50], manufacturing companies [30], family businesses [48], and technology start-ups [49].…”
Section: Ideation (Strategy Definition) Stagementioning
confidence: 99%
See 1 more Smart Citation
“…The external factors are associated with new market opportunities [47,50], institutional change [44], technological innovation [31,35,43], and other perspectives of the industry [34]. These studies are associated with the energy sector [50], manufacturing companies [30], family businesses [48], and technology start-ups [49].…”
Section: Ideation (Strategy Definition) Stagementioning
confidence: 99%
“…Transformative sustainable business models [46] 2023 action research Motivations and challenges of using IoT sensors to reduce food waste [47] 2023 mixed study The interplay of artificial intelligence, the IoT edge, and impact resilience [48] 2022 questionnaire Technology startup business models utilizing knowledge management systems [49] 2022 interview Business model innovation in the energy sector [50] •…”
mentioning
confidence: 99%
“…Secondly, the exploration of additional mediating variables between entrepreneurial failure experiences and re-entrepreneurship performance can provide a more comprehensive understanding of the impact mechanisms. Lastly, interdisciplinary collaborative research can be conducted, considering the widespread application of artificial intelligence, especially its role in enterprises [33] , using diverse research methods from different disciplines to study entrepreneurs' experiences of failure. This will enrich theoretical research and provide practical guidance for entrepreneurial practice.…”
Section: Contributionsmentioning
confidence: 99%
“…Saleem et al(2023) revealed that AI adoption strengthens adaptive resilience and moderates the role of IoT edge in German family-owned SMEs [ 18 ]. Ghobakhloo (2020) identifies factors influencing the implementation of Information and Digital Technologies (IDT) in smart manufacturing and highlights the importance of digital technology and management support [ 19 ]. Skare et al(2023) used the Digital Economy and Society Index (DESI) to explore how digital transformation impacts SMEs and found SMEs benefit from the collective pool of digital knowledge [ 20 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%